Limited asset market participation: does it really matter for monetary policy? - Guido Ascari; Andrea Colciago; Lorenza Rossi (Bank of Finland, 2011)
We study the design of monetary policy in an economy characterized by staggered wage and price contracts together with limited asset market participation (LAMP). Contrary to previous results, we find that once nominal wage stickiness, an incontrovertible empirical fact, is considered: i) the Taylor Principle is restored as a necessary condition for equilibrium determinacy for any empirically plausible degree of LAMP; ii) the implications of LAMP for the design of optimal monetary policy are minor; iii) optimal interest rate rules become active no matter the degree of asset market participation. For these reasons we argue that LAMP is not particularly important for monetary policy.
URN:NBN:fi:bof-20140807429
Keywords: 330